Group model building: a collaborative modelling methodology applied to critical infrastructure protection. (1st January 2012) - Hernantes, Josune; Labaka, Leire; Laugé, Ana; Sarriegi, Jose María; Gonzalez, Jose Julio
Large crises management, affecting CIs needs multidisciplinary knowledge including technical, economical, social, political, legal and managerial knowledge. Being these crises international a huge variety of agents is involved in their response. This situation concludes in a set of stakeholders who only have fragmented knowledge. In the presence of dispersed and incomplete knowledge, and of fragmented and disrupted crisis management, the collaborative approach group model building (GMB), where modelling experts unify fragmented, tacit knowledge from domain experts, is a valuable option. However, GMB has been little used in CIP. We have done so in the context a European project on crisis management of large-scale power cut crises. Particulars in CIP – variety of time horizons, different national perspectives, and challenges to create an international approach, among others – require adaptations in the GMB approach. This paper describes such adaptations and provides insights for better future collaborative modelling.